High selectivity to hydrogen on the methane decomposition over Rh/γ-Al2O3–Nd2O3 catalysts. (28th December 2016) - Caballero, M.; Del Angel, G.; Bonilla-Sánchez, A.; Rangel-Vázquez, I.; Arrieta, A.; Vázquez-Zavala, A.; Huerta, L.; Salgado, M.
Abstract: Methane decomposition was carried out on Rh/γ-Al2 O3 and Rh/γ-Al2 O3 –Nd2 O3 catalysts to produce hydrogen. γ-Al2 O3 –Nd2 O3 mixed oxides and Rh/γ-Al2 O3 –Nd2 O3 catalysts were prepared by wet impregnation using Nd(NO3 )3 ·6H2 O and RhCl3 ·3H2 O as precursors. The concentrations for the catalysts were 1.0 wt% for Rh and 1 and 10 wt% for Nd. The reaction was carried out from 400 to 750 °C. All catalysts showed high activity and selectivity at 700 °C, with conversions around 74–79 vol%. The activity per site (TOF) was higher on Rh crystallites size ≥2.1 nm. The Rh catalyst with 10 wt% neodymium concentration was highly selective to hydrogen, 100%. This behavior was explained by the highest interaction between Rh and γ-Al2 O3 –Nd2 O3 supports. Rh/γ-Al2 O3 and Rh/γ-Al2 O3 –Nd2 O3 with 1 wt% Nd showed selectivities of 89 and 65% at 700 °C respectively and ethane and ethylene products. These products come from the mobility of CHx species on the Rh surface during the reaction. The carbon produced was mainly deposited on the support. Characterization was done by XRD, N2 adsorption isotherms, HRTEM, EDS-SEM, CO-FTIR, H2 -TPR, XPS. Graphical abstract: Highlights: Rh/Al2 O3 –Nd10wt% catalyst showed 100% selectivity to H2 at 700 °C. All Rh catalysts converted around 74–79 vol% at 700 °C. The Rh/Al2 O3 and Rh/Al2 O3 –Nd1wt% produced H2, ethane and ethylene. The carbon formed on Rh/Al2 O3 –Nd2 O3 10wt% after reaction was amorphous carbon.